2023
DOI: 10.47709/cnahpc.v5i1.2150
|View full text |Cite
|
Sign up to set email alerts
|

My Bengkel Application to Facilitate Bookkeeping for Small and Medium Enterprises in the Automotive Sector

Abstract: Small and Medium Enterprises (SMEs) are an important part of the economy of a country or region, as well as in Indonesia, these SMEs play a very important role in the speed of the people's economy. These SMEs are also very helpful to the state/government in terms of creating new jobs and through SMEs many new work units are created that use new workers who can support household income. Simple bookkeeping is a standard that must be owned by all SME business people. It is often found that small business actors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Multiple studies conducted in Indonesia have examined the issue of record-keeping within the MSME sector. These studies, like Jaswadi et al (2015), Lisjanto (2018), and Widayati et al (2023), have consistently found that a significant number of MSMEs in Indonesia continue to face challenges in accurately documenting their financial transactions, which subsequently hinders their ability to meet their tax obligations.…”
Section: Introduction 11 Research Backgroundmentioning
confidence: 99%
“…Multiple studies conducted in Indonesia have examined the issue of record-keeping within the MSME sector. These studies, like Jaswadi et al (2015), Lisjanto (2018), and Widayati et al (2023), have consistently found that a significant number of MSMEs in Indonesia continue to face challenges in accurately documenting their financial transactions, which subsequently hinders their ability to meet their tax obligations.…”
Section: Introduction 11 Research Backgroundmentioning
confidence: 99%